RESILIENCE AND ADAPTABILITY IN CIVIL ENGINEERING EDUCATION: EVALUATING THE IMPACT OF TRANSITIONING FROM ONLINE TO FACE-TO-FACE ASSESSMENTS DURING COVID-19 - Muhamad Faizal Pakir Mohamed Latiff; Nor Hafida Hashim; Mohd Azrizal Fauzi; Md Rasul Mohamad Nor; Anas Ibrahim (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The COVID-19 pandemic necessitated an abrupt shift from in-person to online education, challenging traditional teaching modalities, especially in practical disciplines like civil engineering. This study evaluates the impact of transitioning from online to face-to-face assessments at Universiti Teknologi MARA (UiTM) Pulau Pinang, focusing on the courses Hydraulics (CEW442) and Engineering Hydrology (CEW541). Using a mixed-methods approach, this research integrates quantitative performance metrics and qualitative feedback from faculty interviews, providing a comprehensive understanding of the transition’s effects on student outcomes. The results reveal significant fluctuations in pass rates and Program Outcomes (POs), particularly PO1, PO2, and PO3, during the 20224 semester, which coincides with the shift back to traditional assessments. The findings suggest that while online platforms facilitated theoretical learning, they fell short in supporting practical components, leading to lower PO attainment and passing rates. The study highlights the need for hybrid educational strategies that enhance resilience and adaptability against future disruptions, specifically through continuous assessment improvements and pedagogical adjustments.